2000
DOI: 10.1007/s004640000168
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon dioxide pneumoperitoneum on free radicals

Abstract: These results indicate that CO2 pneumoperitoneum applied with 5-10 mmHg pressure increases the formation of free oxygen radicals by inhibiting SOD activity and that the accumulation of free radicals elevates the level of MDA, a metabolite of lipid peroxidation. The effect of CO2 pneumoperitoneum on free radicals and lipid peroxidation is pressure-dependent in rats. The mechanism underlying this pressure dependency is still under investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In addition, it is easily eliminated from the bloodstream through increased ventilation [3]. However, in recent years, many studies have shown that laparoscopic surgery may cause transient or persistent side effects in intra-abdominal or extra-abdominal organs that are closely related to the type, temperature, and pressure level of the gas used and the duration of the application [2][3][4][5]. Although some of these studies are extreme research models, it is known that stimulated immune response, cytokine releases in response to free radicals production, and ischemia/reperfusion model occur in almost all cases [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it is easily eliminated from the bloodstream through increased ventilation [3]. However, in recent years, many studies have shown that laparoscopic surgery may cause transient or persistent side effects in intra-abdominal or extra-abdominal organs that are closely related to the type, temperature, and pressure level of the gas used and the duration of the application [2][3][4][5]. Although some of these studies are extreme research models, it is known that stimulated immune response, cytokine releases in response to free radicals production, and ischemia/reperfusion model occur in almost all cases [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…The immediate consequences of this relative ischemia were an elevation of various hepatic enzymes, including GOT (glutamic oxaloacetic transaminase) and GPT (glutamic pyruvic transaminase), reflecting hepatocytic damage [90], an impaired function of the Kupffer cells [91], a drop in gastric intramucosal pH [92], an increase in bacterial translocation from the gut, and an increased production of oxygen-derived free radicals [93]. These experimental results were obtained using intra-abdominal pressures ranging from 7 to 30 mm Hg.…”
Section: Splanchnic Ischemiamentioning
confidence: 99%
“…The dismutation of free oxygen radicals with SOD leads to the creation of H 2 O 2 . H 2 O 2 plays an important role as a free radical with different intra-abdominal pressures during CO 2 PP [56]. The activity of SOD would decrease after oxygen radicals are cleaned in liver tissues, indicating that the number of oxygen radicals is increased after CO 2 PP [57].…”
Section: Discussionmentioning
confidence: 98%